Role of Dermatoporosis as Mediating Factors: Impact of Systemic Health Parameters on Dermatology Life Quality Index in The Elderly - W., Linda Julianti; Destra, Edwin; Firmansyah, Yohanes; Moniaga, Catharina Sagita; Tan, Sukmawati Tansil; Wijaya, Bryan Anna; Gunaidi, Farell Christian (Universitas Malahayati, 2026)
ABSTRACT Dermatoporosis, an emerging concern in geriatric dermatology characterized by pronounced skin fragility and chronic skin atrophy, significantly impacts the quality of life among the elderly. This study delves into the complex interactions between various health parameters such as albumin, glucose, lipid profiles, uric acid, vitamin D, insulin resistance, uric acid, renal functions, and liver functions, assessing their cumulative effect on the Dermatology Life Quality Index (DLQI) in an elderly population, with dermatoporosis serving as a pivotal mediating factor. This study included 31 individuals who met the specified inclusion criteria. The selection process was designed to ensure the relevance of analyzed health parameters and to minimize selection bias, thereby enhancing the validity and applicability of the findings. Descriptive and inferential statistical methods were employed, along with Partial Least Squares (PLS) path modeling, to control for potential confounding variables and explore the multifactorial relationships among the measured variables. Regression analysis indicated that dermatoporosis significantly mediates the relationship between these health parameters and the DLQI, evidenced by R² values of 0.691 for dermatoporosis and 0.842 for DLQI. This study confirms that skin health in the elderly is multifactorial and strongly influenced by systemic health parameters. A multidisciplinary approach is essential to holistically manage dermatological conditions, addressing not only skin symptoms, but also systemic health factors that exacerbate skin disorders and diminish the quality of life in older adults. Keywords: Dermatoporosis, Dermatology Life Quality Index (DLQI), Geriatric Dermatology, Health Parameters, Systemic Health Influences.